Pengaruh Premi, Hasil Investasi dan Risk Based Capital terhadap Laba Perusahaan Asuransi Syariah Indonesia 2019 - Nur Indah Aulia Hidayat; Santi Susanti; Sri Zulaihati (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aims to identify whether there is an effect between premiums, investment returns, and risk-based capital on profits in sharia insurance entities in Indonesia in 2019. Research Methodology: The research method applied was quantitative. The affordable population in this study was 45 sharia insurance entities registered with OJK 2019. The sample used was 40 entities by applying the simple random sampling technique. The data analysis technique applied is a multiple linear regression test assisted by IBM SPSS Statistics 26. Results: By using the multiple linear regression analysis methods, the results of this study are that the premium has a positive and significant effect on profits, while investment returns and risk-based capital have Indonesia significant effect on profits. These results can contribute to sharia insurance companies developing the company’s premiums in increasing their profits. Limitations: The research objects used the 2019 period only. Therefore, it is appropriate for the next researcher to continue research with a larger range of research subjects and add other variables. Contribution: The results of this study can be useful for all insurance companies to create strategies in obtaining profits from several factors that have been studied.